Case study: Resumption of eumenorrhea in parallel with high training load after 4 years of menstrual dysfunction: A 5-year follow-up of an elite female cyclist - Areta, J. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
The female athlete triad is a condition where low energy availability is typically observed together with menstrual dysfunction and/or low bone mineral density. How this condition affects maximal work capacity in endurance athletes is not clear, and the recovery time course of menses with increased energy availability with concomitant high training load is unknown. This case study of an amenorrheic elite road cyclist reports resumption of normal menstrual function after weight gain during a 5-year period (2014-2019), while engaged in high training load and competition. The athlete (VO2max 3.54 L/min, 64 ml·min-1·kg-1, aerobic peak power output 300 W, 5.4 W/kg) reported amenorrhea (2013-2015) and oligomenorrhea (2015-2018). Training load increased from 2014 to 2019 (584-818 hr/year and 26,707-41,945 training stress score/year). Regular menses (every 23-35 days) resumed in June 2018, ~5-6 months after a weight gain episode. During the period of menstrual dysfunction, body mass was 51.3 ± 2.25 kg (mean ± 95% confidence limit) and fat percentage was 19% (dual-energy X-ray absorptiometry, 2016), and after weight gain, body mass was 56.8 ± 2.63 kg and fat percentage was 25% (dual-energy X-ray absorptiometry, 2019). Crank-based power meter data showed absolute mean maximal power (in watts) improvement over the 5 s to 4 hr range through the 2014-2019 period, while relative mean maximal power (in watts per kilogram) likely peaked in the 2015-2016 season for 5 min, 20 min, and 30 min, but remained mostly unchanged across seasons. Results suggest that (a) the best relative power output associated with aerobic capacity (5 min to 1 hr) can be achieved during menstrual dysfunction, (b) high performance achieved despite an increase in body mass, and (c) resumption of menses is achievable while maintaining high training loads when coupled with high energy availability.